Robot-assisted concept for assembling form coils in laminated stator cores of large electric motors - Mahr, Alexander; Mayr, Andreas; Jung, Timo; Franke, Jörg (Procedia Manufacturing, 2019)
Manufacturers of large electric motors, whether for automation or traction purposes, are facing major challenges in high-wage countries. Due to the high proportion of manual activities, a conflict between ensuring profitability and increasing variant variety arises. In order to meet the high demand for large electric motors and to maintain the value added in high-wage countries, manual manufacturing processes must be automated, at least partially. For large electric motors with form coil technology, especially the assembly into the laminated stator core represents a tedious, cost-intensive manual activity. Therefore, this paper deals with the development of a hybrid, robot-assisted assembly system for inserting form coils in laminated stator cores. The combination of manual and automated assembly activities is intended to ensure high productivity while maintaining flexibility. Before realizing such a hybrid assembly system, all process steps are simulated first. In addition, additive manufacturing is used to quickly produce and practically validate different end effector geometries. As shown by the final prototypical implementation, a major portion of the assembly of form coils can be carried out fully automatically by a dual-arm robot. Remaining challenges could be addressed by adding a vision system and thereby making use of novel machine learning techniques.<br
Keywords: Hybrid assembly system; Automation; Dual-arm robot; Electric motor production; Form coils; Stator production